IN VITRO INHIBITION OF SPERMATOGENESIS WITH CHITOSAN NANOPARTICLES CONTAINING PHYLLANTHUS NIRURI EXTRACT THROUGH FGF2 GENE EXPRESSION ANALYSIS USING QPCR METHOD - Fitria Chasanah, Rizka
Phyllanthus niruri (P. niruri), or commonly known as 'meniran,' is a plant often utilized in traditional medicine. Encapsulation of P. niruri extract using chitosan nanoparticles has been shown to be beneficial as a co-adjuvant in enhancing the immune response to orally administered HBsAg antigen. The oral use of P. niruri extract is not cytotoxic and genotoxic, but it can influence the hormonal system, affecting processes such as spermatogenesis and potentially leading to male infertility. This study aims to determine the effects of using empty chitosan nanoparticles, chitosan nanoparticles containing P. niruri extract, and P. niruri extract across a range of concentrations 7,81 ppm; 15,62 ppm; 31,25 ppm; 62,50 ppm; 125 ppm; 250 ppm; 500 ppm; 1000 ppm and 2000 ppm on the expression ratio of the Fgf2 gene, which is involved in the non-classical testosterone signaling pathway. Chitosan nanoparticles were produced using the ionic gelation method, characterized, and then tested for the inhibition of Fgf2 gene expression using qPCR on TM4 cell lines. The results showed that the administration of chitosan nanoparticles did not significantly inhibit the transcription of the Fgf2 gene. However, the administration of chitosan nanoparticles containing P. niruri extract at concentrations of 500 ppm, 1000 ppm, and 2000 ppm, as well as P. niruri extract at 2000 ppm without encapsulation, resulted in a significant inhibition of Fgf2 gene transcription. In conclusion, both P. niruri extract and encapsulated P. niruri extract within chitosan nanoparticles can lead to the inhibition of Fgf2 gene transcription, thereby disrupting spermatogenesis through reduced sperm motility, meiosis inhibition, and hindered regeneration of spermatogonial stem cells (SSC).